Hadith in the Ancient Schools of Law According to Joseph Schacht - Riady, Fahmi; Nadhiroh, Wardatun; Khairuddin, Abdul Karim bin (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
In the 3rd century H, the traditions of the Prophet have been collected. In the sixth book (al-Kutub as-Sittah), only the traditions of the Prophet are prioritized. Before Asy-Syāfi‘ī (d. 204 H), in the ancient schools of law, the traditions of the Prophet received little attention. Based on this problem, the author explores further how the hadith in ancient schools of law was, according to Schacht. From two of Schacht's works, An Introduction to Islamic Law and The Origins of Muhammadan Jurisprudence, the author focuses on: 1). The ancient school of law according to Joseph Schacht; and 2). Hadith in ancient schools of law, according to Joseph Schacht. This discussion aims to describe Schacht's ideas about ancient schools of law and how ancient schools of law use hadiths. In this article, the author uses a qualitative descriptive approach, using documentary methods and historical analysis. The study results show that in the history of the development of legal doctrine, ancient schools of law were born from the activities of qādī (Islamic judges) and specialists concerned with legal issues. Their distinctive feature is geographical differences: Hijaz (Makkah and Medina), Iraq (Kufah and Basra), Syiria, and Egypt. Their response to the widespread practice and administrative regulations of the Umayyad dynasty (collapsed 132 H) gave birth to what is known as Islamic law. During the Abbasid dynasty, the ancient school of law changed into a new school of law based on loyalty to a teacher, which in turn formed groups such as the followers of Abū Ḥanīfah (d. 150 H), Mālik (d. 179 H), Sufyān aṡ-Ṡaurī ( d. 161 H), al-Auzā’ī (d. 157 H), and so on. The ancient legal schools had the same attitude towards hadith. They prioritize the Companions' traditions rather than the Prophet's traditions. This can be seen from Asy-Syāfi‘ī's polemic against the Medina and Iraqi schools. Other evidence is the distribution of the use of hadiths of the Prophet and traditions other than the Prophet in the book al-Muwaṭṭa’, Ᾱṡār Abū Yusūf and Ᾱṡār ash-Syaibānī